Interrupting long periods of sitting: good STUFF - Rutten Geert M; Savelberg Hans H; Biddle Stuart JH; Kremers Stef PJ (BMC, 2013)
Abstract There is increasing evidence that sedentary behaviour is in itself a health risk, regardless of the daily amount of moderate to vigorous physical activity. Therefore, sedentary behaviour should be targeted as important health behaviour. It is known that even relatively small changes of health behaviour often require serious efforts from an individual and from people in their environment to become part of their lifestyle. Therefore, interventions to promote healthy behaviours should ideally be simple, easy to perform and easily available. Since sitting is likely to be highly habitual, confrontation with an intervention should almost automatically elicit a reaction of getting up, and thus break up and reduce sitting time. One important prerequisite for successful dissemination of such an intervention could be the use of a recognisable term relating to sedentary behaviour, which should have the characteristics of an effective brand name. To become wide spread, this term may need to meet three criteria: the "Law of the few", the "Stickiness factor", and the "Power of context". For that purpose we introduce STUFF: Stand Up For Fitness. STUFF can be defined as "interrupting long sitting periods by short breaks", for instance, interrupting sitting every 30 min by standing for at least five minutes. Even though we still need evidence to test the health-enhancing effects of interrupted sitting, we hope that the introduction of STUFF will facilitate the testing of the social, psychological and health effects of interventions to reduce sitting time.